2017
DOI: 10.1016/j.colsurfa.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Yielding and flow of foamed metakaolin pastes

Abstract: Metakaolin is a broadly used industrial raw material, with applications in the production of ceramics and geopolymers, and the partial replacement of Portland cement. The early stages of the manufacturing of some of these materials require the preparation and processing of a foamed metakaolinbased slurry. In this study, we propose to investigate the rheology of a foamed metakaolin-based fresh paste by performing well-controlled experiments. We work with a non-reactive metakaolin paste containing surfactant, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Results (figure 4) have shown that the yield stress of emulsion foams depends on coupled effects of capillary pressure, 8 ⁄ , and emulsion yield stress, . Those parameters can be used to form the Bingham-capillary number [25,26,29], <= = 8 ⁄ . The reduced yield stress…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results (figure 4) have shown that the yield stress of emulsion foams depends on coupled effects of capillary pressure, 8 ⁄ , and emulsion yield stress, . Those parameters can be used to form the Bingham-capillary number [25,26,29], <= = 8 ⁄ . The reduced yield stress…”
Section: Discussionmentioning
confidence: 99%
“…In fact, little is known about rheology of complex liquid foams while such knowledge is crucial for applications. Yield stress properties allow the material to sustain external forces and to keep its initial shape under gravity [25,27,29]. For example, the thickness of a material layer that can be deposited on vertical substrates is directly related to the material yield stress and effective material density.…”
Section: Introductionmentioning
confidence: 99%
“…In the elaboration of optimized foamed materials, the rheological behavior of those complex foams is also of primary interest. For example, elasticity and yield stress properties allow the material to sustain external forces and to keep its initial shape under gravity [20][21][22]. In contrast, filling of molds requires an appropriate workability of the fresh foamy paste.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were mainly focused on drainage and stability issues [4][5][6][7][8][9][12][13][14][15][16][17]19,20 because those two processes jeopardize fresh (not solidified) foamed materials. In contrast, only few studies have tackled rheological issues, for all types of foamed suspensions 5,12,13,22,23,[25][26][27][28][29][30] . However, in the elaboration of optimized foamed materials, the rheological behavior of fresh complex foam is of primary interest also.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the elaboration of optimized foamed materials, the rheological behavior of fresh complex foam is of primary interest also. For example, elasticity and yield stress properties allow the material to sustain external forces and to keep its initial shape under gravity 26,27,29 . In contrast, filling of molds requires appropriate workability of the fresh foamy material.…”
Section: Introductionmentioning
confidence: 99%